Germinación de semillas después del fuego: Un estudio con una planta que habita áreas no propensas al fuego - Menezes, L. C. C. R. de [UNESP]; Rossi, M. N. (My University, 2011)
After a fire event, germination of seeds with hard coats can be enhanced. In the present study, we investigated whether germination of Mimosa bimucronata (DC.) Kuntze (Fabaceae) seeds, which present hard coats, is increased after fire, even though these trees usually occur in damp areas, where fire is a transient event. Fire events were manipulated in trays filled with soil covered with different amounts of dry grasses, characterizing three treatments: a) 0g (control group); b) 300g, and c) 450g of dry grass. Burning treatments were applied to seeds positioned either on the soil surface or buried in the soil. Germination experiments were carried out at 0-h and 24-h after fire to obtain the germination percentage and the Germination Speed Index (GSI). For buried seeds, the control and the 300g treatments presented significantly higher germination percentages than the 450g treatment. On the other hand, the GSI was significantly higher in the 300g treatment. Significant differences were not found between 0-h and 24-h. Seeds on the soil surface did not survive after burning. Our study showed that temperatures around 100 °C significantly decrease the germinability of M. bimucronata seeds. However, when seeds were buried, the germination percentage did not differ between the control group and the 300g treatment. Results also suggest that temperatures around 60 °C may enhance the velocity of germination of M. bimucronata seeds.
Seed germination after fire: A study with a plant inhabiting non-fire-prone areas
Keywords: Fabaceae; Germination; Hard seed coat; High temperatures